Guidelines or commandments? Reconsidering core principles in extensive reading - Macalister, John (Reading in a foreign language, 2015)
Macalister offers clarification on the 10 principles of extensive reading (ER). Extensive reading is not a difficult concept but suffers at times from being differently understood by teachers and researchers, leading to some confusion in the literature surrounding it, and at other times suffers from attempts to over-complicate it. In this paper he attempted to de-mystify extensive reading, drawing onand reducing in numberthe principles proposed by Day and Bamford (2002) over a decade ago. These principles, and those proposed by Williams (1986) for teaching reading almost two decades earlier, continue to provide a sound basis for understanding and implementing successful reading practices in the language classroom.